Building within space: thoughts towards an environmental ethics - Paddock, Troy (Ethics in Progress, 2014)
The need for constructing an environmental ethics that keeps sustainability in mind is the result of a collision of the realization that the natural environment is neither limitless nor impervious to actions with a view of nature that has been fundamentally instrumentalist and anthropocentric. This paper will borrow from architectural theory in an effort to do two things: First, it will point to some of the limitations of an anthropocentric view of nature and how it impacts efforts to influence environmental policy; second, it will suggest that ideas from Aristotle and Actor Network Theory can help to provide a paradigm within which we can think about nature in a way that offers an alternative framing of questions about the environment.
0 citations (Crossref) [2023-10-31]
Keywords: dept.his